2000
DOI: 10.1128/jb.182.18.5251-5255.2000
|View full text |Cite|
|
Sign up to set email alerts
|

The Amino Terminus of Pseudomonas aeruginosa Outer Membrane Protein OprF Forms Channels in Lipid Bilayer Membranes: Correlation with a Three-Dimensional Model

Abstract: Pseudomonas aeruginosa OprF forms 0.36-nS channels and, rarely, 2-to 5-nS channels in lipid bilayer membranes. We show that a protein comprising only the N-terminal 162-amino-acid domain of OprF formed the smaller, but not the larger, channels in lipid bilayers. Circular dichroism spectroscopy indicated that this protein folds into a ␤-sheet-rich structure, and three-dimensional comparative modeling revealed that it shares significant structural similarity with the amino terminus of the orthologous protein Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 22 publications
3
35
0
1
Order By: Relevance
“…Since the major outer membrane protein OprF is thermo-sensitive [8,17], exhibits extracellular domains, such as the variable loops exposed to the cell surface [4], and is described as an adhesin in the rhizosphere [9], we investigated its involvement in the physicochemical properties of the P. Xuorescens cell surface and in its adhesive behavior. We constructed a stable OprF-lacking P. Xuorescens mutant: strain MF373 [7].…”
Section: Resultsmentioning
confidence: 99%
“…Since the major outer membrane protein OprF is thermo-sensitive [8,17], exhibits extracellular domains, such as the variable loops exposed to the cell surface [4], and is described as an adhesin in the rhizosphere [9], we investigated its involvement in the physicochemical properties of the P. Xuorescens cell surface and in its adhesive behavior. We constructed a stable OprF-lacking P. Xuorescens mutant: strain MF373 [7].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 5c, both monomeric units of the dimer are oriented parallel to one another with their N-terminal ends that would connect to the membrane-bound β-barrel region extended towards the outer membrane (Brinkman et al, 2000) while their C-terminal globular regions reside in the periplasmic space. The putative PG-binding sites ( highlighted in blue, 5c ) of OprF are located within the periplasmic region in the top dimer model.…”
Section: Discussionmentioning
confidence: 99%
“…Structure and function of OprF: Modelling studies carried out by Brinkman et al, [38] showed that OprF lacks the salt bridges associated with closure of the OmpA channel allowing for a larger channel, relative to OmpA. More recently, it has been shown that both OmpA and OprF exist in two conformers, the majority of molecules exist in an eight barrel structure in a closed channel with the C-terminus domain in the periplasm interacting with peptidoglycan [39].…”
Section: Oprf -The Ompa Ortholog In P Aeruginosamentioning
confidence: 98%